2015
DOI: 10.1016/j.archoralbio.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers of periodontitis and/or obesity in saliva—An exploratory analysis

Abstract: Objective Recent studies point to the clinical and research utility of saliva as a valuable diagnostic aid for monitoring periodontal health. The objectives of this study were to detect novel biomarkers attributed to chronic inflammation in saliva and to determine if the levels of these markers correlate with severity of periodontitis and with standard obesity measures in participants in a periodontal maintenance program. Design In this cross-sectional assessment of 63 participants, unstimulated whole saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In addition, BMI and WHR positively correlated with the number of PPD with 4–5 mm and with 6 mm or more in the present study. Recker et al , reported that waist circumference, but not BMI and fat%, was positively correlated with the severity of periodontitis, whereas Saxlin et al , found that all three parameters were positively correlated with the number of teeth with deepened periodontal pockets. These findings could be interpreted to indicate that increased body weight has a detrimental effect on periodontal status.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BMI and WHR positively correlated with the number of PPD with 4–5 mm and with 6 mm or more in the present study. Recker et al , reported that waist circumference, but not BMI and fat%, was positively correlated with the severity of periodontitis, whereas Saxlin et al , found that all three parameters were positively correlated with the number of teeth with deepened periodontal pockets. These findings could be interpreted to indicate that increased body weight has a detrimental effect on periodontal status.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of periodontal probes, and radiography could only provide information about previous periodontal damage rather than the current state [93]. Thus, biomarkers have been proposed as complementary methods to defeat the mentioned limitations monitoring the clinical response to an intervention and future risk [95].…”
Section: Discussionmentioning
confidence: 99%
“…Infection of HOK with either T. forsythia ATCC 43037 or UB4, also induced the release of IL‐1Ra, an anti‐inflammatory cytokine blocking ligand receptor binding of IL‐1β . Levels of IL‐1Ra are increased in gingival crevicular fluid from periodontitis patients and IL‐1Ra levels in saliva have been shown to correlate with the severity of the disease; however, induction of IL‐1Ra by T. forsythia has not been described.…”
Section: Discussionmentioning
confidence: 99%